Changing entrepreneurial attitudes for mitigating the global pandemic’s social drama - Elena G. Popkova (Humanities & Social Sciences Communications, 2022)
Abstract This paper investigates international experiences and perspectives on how entrepreneurs can improve management practices while minimizing the COVID-19 pandemic’s social drama. The paper probes how companies deal with the myriad challenges they face amid the unfolding pandemic and how these processes’ economic and cultural dimensions may exert an enduring effect. A novel dataset analyses how entrepreneurs manage the change of management processes in a sample of ten countries. Three economic impacts on entrepreneurs caused by the pandemic were observed: (1) a deficit as a result of social distancing reduced due to the growth of Internet retailing; (2) a deficit resulting from a fall in demand decreased due to innovations that mitigate this demand-side change; (3) a social crisis in the labour market due to social distance and relocating many employees to remote working practices. In countries with the most considerable number of cases of COVID-19, it is recommended that attitudes towards entrepreneurial risk be raised. In countries with the vastest number of fatal cases per 100,000 people, implications for change management in entrepreneurship are an increase in Internet retailing level, a reduction in entrepreneurial fear of failure, and an increase in entrepreneurial risk awareness. Besides, an anonymous sociological survey among companies’ directors and managers in Russia on management initiatives taken on between late 2020–early 2021 shows that companies maintain a 60.21% readiness for such systemic challenges while their readiness for change increased under the influence of the pandemic. The contribution to the literature of this article lies in rethinking the COVID-19 crisis from the standpoint of social drama, which made it possible to clarify the cause-and-effect relationships of change management in entrepreneurship. For the first time, the paper proposes systemic—socio-economic recommendations for improving the practice of change management against the background of such a social drama.